2013
DOI: 10.2478/jeb-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Commodity Price Volatility during and after the Economic Crisis – Implications for Romania

Abstract: Under the impact of a wide range of forces, the prices of globally traded commodities often experience sudden and significant fluctuations, putting under uncertainty and risk the economic status of producers, consumers and traders from the private to the national level. Although commodity markets are notorious for their price volatility, the events the world economy experienced in recent years, particularly the global economic crisis, offered new connotations to this phenomenon. These price movements reverbera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Over the last decade or so, commodity markets at the global level have experienced profound turbulence and significant volatility (Pop et al , 2013). It is shown that commodity volatility relates to unpredictability of market fundamentals, and retail price spikes arise when these phenomena occur.…”
Section: Meat Avoidance and Reduction With Retail Price Volatilitymentioning
confidence: 99%
“…Over the last decade or so, commodity markets at the global level have experienced profound turbulence and significant volatility (Pop et al , 2013). It is shown that commodity volatility relates to unpredictability of market fundamentals, and retail price spikes arise when these phenomena occur.…”
Section: Meat Avoidance and Reduction With Retail Price Volatilitymentioning
confidence: 99%
“…Given that a larger percentage of ECOWAS population engage in agricultural activity, it is obvious that many face uncertainty in their future income. Interestingly, researchers have pointed out that price fluctuations occasioned by the recent global financial crisis, increased uncertainty and risk and affected the economic status of commodity producers, consumers and traders (Pop, Rovinaru, and Rovinaru 2013). Skinner (1988) suggested that greater uncertainty about future incomes compels consumers to set aside some resources for precautionary purposes.…”
Section: Theoretical Framework and Modelmentioning
confidence: 99%
“…economic recession or the importing country experiences a severe crisis. This influence causes a decrease in demand both domestically and abroad (Pop et al, 2013;Rahmadi, 2012). The long-term effect of this problem leads to sluggish exports to other countries (Kumar, 2011).…”
Section: Introductionmentioning
confidence: 99%